Discovery and characterization of [(cyclopentyl)ethyl]benzoic acid inhibitors of microsomal prostaglandin E synthase-1. Issue 6 (15th March 2017) - Partridge, Katherine M.; Antonysamy, Stephen; Bhattachar, Shobha N.; Chandrasekhar, Srinivasan; Fisher, Matthew J.; Fretland, Adrian; Gooding, Karen; Harvey, Anita; Hughes, Norman E.; Kuklish, Steven L.; Luz, John G.; Manninen, Peter R.; et al.
Graphical abstract: Abstract: We describe a novel class of acidic mPGES-1 inhibitors with nanomolar enzymatic and human whole blood (HWB) potency. Rational design in conjunction with structure-based design led initially to the identification of anthranilic acid5, an mPGES-1 inhibitor with micromolar HWB potency. Structural modifications of5 improved HWB potency by over 1000×, reduced CYP2C9 single point inhibition, and improved rat clearance, which led to the selection of [(cyclopentyl)ethyl]benzoic acid compound16 for clinical studies. Compound16 showed an IC80 of 24 nM for inhibition of PGE2 formation in vitro in LPS-stimulated HWB. A single oral dose resulted in plasma concentrations of16 that exceeded its HWB IC80 in both rat (5 mg/kg) and dog (3 mg/kg) for over twelve hours.